ASSESSMENT OF NUTRITIONAL STATUS BASED ON BMI OF LODHA TRIBAL WOMEN IN MAYURBHANJ DISTRICT OF ODISHA - JHUNILATA BHUYAN*, SASMITA BEHERA and DEEPAK KUMAR MOHANTY, (The Journal of Research ANGRAU, 2021)
Mayurbhanj is a tribal dominated district and Lodha is a primitive vulnerable tribe of this district.Very scanty information about their nutritional, dietary pattern and dietary habits was reported. Hence,this study was conducted in 2019-20 and 2020-21 to assess the nutritional status of the Lodha tribalwomen, so that it will be helpful for planning and monitoring programmes for the betterment of LodhaTribal women.The respondents were selected randomly from ten villages of Moroda, Suliapada,Baripada and Shamakhunta. The study revealed that the average height of the Lodha tribal womenwas 146.6± 5.4 cm, body weight was 37.8 ± 6.31 kg, waist circumference was 78.3± 7.87 cm, hipcircumference was 77.3 ±8.83 cm, mid arm circumference was 20.6 ± 2.21 cm, BMI was 17.6± 2.8kg/m2, waist hip ratio was 20.7± 2.21 cm. At the aggregate level 27.3 percentage of tribal womenshowed normal range of BMI value (18.5-22.9 kg/m2) but 68.7% of the Lodha tribal women comeunder underweight ( 18.5 kg/m2) category of BMI classification.Only 2% of Lodha tribal womenrepresented both over weight (23.0-24.9 kg/m2) and obese ( 25.0kg/m2) category of Chronic EnergyDeficiency (CED), this showed the tribal society was also stepping towards dual burden ofmalnourishment and overweight among Lodha tribal women. The research also revealed that therewas statistically significant association between income with BMI and education with BMI, however,statistically non-significant association between age with BMI and types of family with BMI.